Skills for human development : transforming vocational education and training - Powell, Lesley, 1966-; McGrath, Simon A. (Routledge, Taylor and Francis Group, 2019)
Focusing on reimagining the purpose of vocational education and training (VET) and grounded in the reality of a small cohort of young South Africans and an institution seeking to serve them, Skills for Human Development moves beyond the inadequacies of the dominant human capital orthodoxy to present a rich theoretical and practical alternative for VET. Offering a human development and capability approach, it brings social justice to the forefront of the discussion of VET's purpose at the national, institutional and individual levels. In doing so, this book insists that VET should be about enlarging peoples' opportunities to live a flourishing life, rather than simply being about narrow employability and productivity. It argues that human development approaches, while acknowledging the importance of work in its broadest sense, offer a better way of bringing together VET and development than the current human capital-inspired orthodoxy. Offering a transformative vision for skills development, this book: Considers the potential contribution skills development could make to broader human development, as well as to economic development Points to an alternative approachto the current and flawed deficit assumptions of VET learners Presents for the first time an alternative evaluative frame for judging VET purpose and quality Presents a timely account of current vocational and education training that is high on the agenda of international policymakers Taking a broad perspective, Skills for Human Development presents a comprehensive and unique framework which bridges theory, policy and practice to give VET institutions a new way of thinking about their practice, and VET policymakers a new way of engaging with global messages of sustainable human development. It is a vital resource for those working on the human development and skills approach in multiple disciplines and offers a grounding framework for international policymakers interested in this growing area.- Resumé vydavatel
Keywords: odborné vzdělávání; profesní příprava; vzdělávací reformy; vocational education; professional training; educational reforms; elektronické knihy; monografie; electronic books; monographs